Aboriginal Concepts of Place and Country and their Meaning in Mental Health - Bishop, Brian John; Vicary, David; Mitchell, J.; Pearson, G. (The College of Community Psychologists of the Australian Psychological Society, 2014)
There is a lack of knowledge within Western psychology about Australian Aboriginal conceptions of mental health. The majority of psychological services available to Aboriginal people are based on Western world-views, and are of questionable benefit. Because of the ethnocentrism apparent inherent in services, many Aboriginal people avoid psychological assistance. If there is to be any change in the state of Indigenous mental health, there needs to be a change in the type of services provided to Aboriginal people, and in the value systems of practitioners. This research extends the work of Vicary (2002) by looking specifically at the importance of place in Aboriginal worldviews. There exists a wide gulf between Aboriginal and non-Aboriginal understandings of mental health, in particular, a culture more generally. Concepts such as ‘country’ need to be understood by non-Aboriginal practitioners for them to be able to provide a quality service that is culturally appropriate.